2008
DOI: 10.1038/nature06548
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to therapy caused by intragenic deletion in BRCA2

Abstract: Cells with loss of BRCA2 function are defective in homologous recombination (HR) and are highly sensitive to inhibitors of poly(ADP-ribose) polymerase (PARP), which provides the basis for a new therapeutic approach. Here we show that resistance to PARP inhibition can be acquired by deletion of a mutation in BRCA2. We derived PARP-inhibitor-resistant (PIR) clones from the human CAPAN1 pancreatic cancer cell line, which carries the protein-truncating c.6174delT frameshift mutation. PIR clones could form DNA-dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
713
4
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 897 publications
(737 citation statements)
references
References 29 publications
17
713
4
3
Order By: Relevance
“…Our results might have direct clinical relevance, because recent trials demonstrated that both HSP90 and PARP-1 inhibitors are generally well tolerated (35,36). Moreover, because our approach is not based on genetic deficiency, as is the case in hereditary BRCA2-deficient tumors, it is not likely that a previously described mechanism of resistance to the inhibitor will be relevant (37,38). Our results could provide a rational basis for development of therapies for a wide range of tumors, exploiting local, on-demand induction of HR deficiency in combination with PARP-1 inhibitors, ionizing radiation, or other DSB-inducing chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 83%
“…Our results might have direct clinical relevance, because recent trials demonstrated that both HSP90 and PARP-1 inhibitors are generally well tolerated (35,36). Moreover, because our approach is not based on genetic deficiency, as is the case in hereditary BRCA2-deficient tumors, it is not likely that a previously described mechanism of resistance to the inhibitor will be relevant (37,38). Our results could provide a rational basis for development of therapies for a wide range of tumors, exploiting local, on-demand induction of HR deficiency in combination with PARP-1 inhibitors, ionizing radiation, or other DSB-inducing chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 83%
“…These may be secondary to contamination by normal cells as described above, or reveal a true difference between germline and tumor DNA suggesting the tumor has undergone a secondary mutation with restoration of the open reading frame and restoration of a functional BRCA1 gene. [62][63][64] We have demonstrated that BRCA abnormalities are only associated with the high-grade serous subtype of ovarian carcinoma. TP53 abnormalities (as detected by immunohistochemistry) and immune cell infiltrates were associated with BRCA mutations; there is at present no data to indicate whether BRCA mutation, TP53 abnormalities, and host immune cell infiltrates, all of which are favorable prognostic factors in univariate analysis in large case series, are of independent prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all patients treated with a PARP inhibitor experienced progression of disease after several months of therapy, despite an initial clinical and radiographic response. The mechanism of acquired resistance in vivo to PARP inhibition is unknown, but it may potentially occur as a result of a secondary mutation resulting in restored competency of homologous repair in BRCA-mutant cells [13].…”
Section: Discussionmentioning
confidence: 99%